2021
DOI: 10.1186/s13063-021-05880-8
|View full text |Cite
|
Sign up to set email alerts
|

A report from the NIHR UK working group on remote trial delivery for the COVID-19 pandemic and beyond

Abstract: Background Prior to the COVID-19 pandemic, the majority of clinical trial activity took place face to face within clinical or research units. The COVID-19 pandemic resulted in a significant shift towards trial delivery without in-person face-to-face contact or “Remote Trial Delivery”. The National Institute of Health Research (NIHR) assembled a Remote Trial Delivery Working Group to consider challenges and enablers to this major change in clinical trial delivery and to provide a toolkit for res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…18,19 In the UK, optimising RCT delivery using remote methods is a key piece of work being developed between research funders and regulators. 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 In the UK, optimising RCT delivery using remote methods is a key piece of work being developed between research funders and regulators. 20…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In the UK, optimising RCT delivery using remote methods is a key piece of work being developed between research funders and regulators. 20 The DISC survey and site investigators meeting identified a number of problems effectively and is an approach recommended for ongoing/future trials. Communication with study sites to identify what barriers exist so that solutions can be developed is a proven effective strategy to improve recruitment rates.…”
Section: Discussionmentioning
confidence: 99%
“…The CRN is an expert in the conduct and adherence to the clinical trial protocol (Godskesen et al, 2018: 475–485). This expert knowledge related to assessments, participant visit schedule and the investigative medicine/device is critical to the safety of the participant (Masoli et al, 2021: 911). As the DCT design enables participants to receive novel treatments via research studies/clinical trials at home, this expert knowledge allows the CRN to accommodate for differences in care delivery environments (home instead of hospital or research centre).…”
Section: Background Of Crn Role With Dctsmentioning
confidence: 99%
“…In the rush to implement remote/virtual trials under the DCT model, there is a paucity of literature surrounding the specific communication skillsets required by CRNs to align with community cultures, participants and varied industry sponsors. Current literature surrounding DCTs omits the description of CRN education requirements unique to DCT conduct compared to on-site research conduct (Apostolaros et al, 2020: 779–787; Masoli et al, 2021: 911). Without familiar equipment, resources or surroundings, research nurses require education relating to home-based nursing and how it complements existing research-based training.…”
Section: Background Of Crn Role With Dctsmentioning
confidence: 99%
“…concerns about digital exclusion of research participants who may not have access to digital tools, and/or internet connections, or lack familiarity with using these platforms (e.g.,1,[16][17][18]. exclusion by providing training on digital tools in various modalities (e.g., videos, face-to-face) to increase research participant's/staff confidence in use and providing a physical location and/or digital tool in order for people to participate in a study.…”
mentioning
confidence: 99%